2017
DOI: 10.1038/tp.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses and leukocyte telomere length measurement in subjects exposed to severe recent stressful life events

Abstract: Stressful life events occurring in adulthood have been found able to affect mood and behavior, thus increasing the vulnerability for several stress-related psychiatric disorders. However, although there is plenty of clinical data supporting an association between stressful life events in adulthood and an enhanced vulnerability for psychopathology, the underlying molecular mechanisms are still poorly investigated. Thus, in this study we performed peripheral/whole-genome transcriptomic analyses in blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…For example, inflammation has been heavily studied in the context of telomere dynamics (Park et al, 2015), but we saw no change after adjustment for c-reactive protein. Future analyses should consider investigating additional inflammatory pathways via biomarkers such as interleukin-6 and tissue necrosis factor alpha (Farzaneh-Far et al, 2010; Lopizzo et al, 2017; Zhang et al, 2016). The literature also highlights differences in telomere dynamics between men and women (Gardner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inflammation has been heavily studied in the context of telomere dynamics (Park et al, 2015), but we saw no change after adjustment for c-reactive protein. Future analyses should consider investigating additional inflammatory pathways via biomarkers such as interleukin-6 and tissue necrosis factor alpha (Farzaneh-Far et al, 2010; Lopizzo et al, 2017; Zhang et al, 2016). The literature also highlights differences in telomere dynamics between men and women (Gardner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A similar association between stress-related cortisol levels and shortened LTL was demonstrated within a small cohort of caregivers (Tomiyama et al, 2012). Transcriptomic analysis revealed an association between alterations in exposure to recent stressful events and several key signaling pathways (involving natural killer cells, interleukin-1, macrophage migration inhibitory factor (MIF)-mediated glucocorticoid and immune regulation, and interleukin-6) that may be responsible for increasing oxidative stress and the resulting damage to telomeres (Lopizzo et al, 2017). Telomeres are thought to be susceptible to oxidative stress due to their high proportion of guanine residues (Mason & Perdigones, 2013; Von Zglinicki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…26 In pro-inflammatory states, macrophages release IL-1β and IL-6, both related to telomere shortening. 27 In the analysis of 87 of the 190 participants of The Harvard Boilermakers Longitudinal Study 28 an association was found between inflammatory parameters and the decrease in telomere length, especially with hsCRP. However, in that study, no significant relationships were found with interleukins, which may be due to the number of patients or the low variability in the plasma concentrations of these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, cumulative inflammatory loads reflected by high levels of inflammation markers such as C-reactive protein (CRP) [27,28], fibrinogen [27], interleukin 6 (IL-6) [28,29,30], and tumor necrosis factor (TNF)-a [30] have been cross-sectionally associated with shorter TL, by a number of studies. Lin and coworkers [31] extended this evidence in a prospective study on a sample of 20 healthy mothers of children with autism (caregivers) and 19 mothers of neurotypical children (controls).…”
Section: Telomeresmentioning
confidence: 99%